An all-in-one numerical methodology for fretting wear and fatigue life assessment - I. Llavori; M.A. Urchegui; W. Tato; X. Gomez (Fracture and Structural Integrity)
Many mechanical components such as, bearing housings, flexible couplings and spines or orthopedic devices are simultaneously subjected to a fretting wear and fatigue damage. For this reason, the combined study on a single model of wear, crack initiation and propagation is of great interest. This paper presents an all-in-one 2D cylinder on flat numerical model for life assessment on coupled fretting wear and fatigue phenomena. In the literature, two stages are usually distinguished: crack nucleation and its subsequent growth. The method combines the Archard wear model, a critical-plane implementation of the Smith-Watson- Topper (SWT) multiaxial fatigue criterion coupled with the Miner-Palmgren accumulation damage rule for crack initiation prediction. Then, the Linear Elastic Fracture Mechanics (LEFM) via eXtended Finite Element Method (X-FEM) embedded into the commercial finite element code Abaqus FEA has been employed to determine the crack propagation stage. Therefore, the sum of the two stages gives a total life prediction. Finally, the numerical model was validated with experimental data reported in the literature and a good agreement was obtained.